Gas turbine sub-idle performance modelling : groundstart altitude relight, and windmilling - Grech, Nicholas (Cranfield University, 2013)
Engine performance modelling is a major part of the engine design process, in which specialist solvers are employed to predict, understand and analyse the engine’s behaviour at various operating conditions. Sub-idle whole engine performance synthesis solvers are not as reliable and accurate as design point solvers. Lack of knowledge and data result in component characteristics being reverse-engineered or extrapolated from above-idle data. More stringent requirements on groundstart and relight capabilities, has prompted the need to advance the knowledge on low-speed engine performance, thereby requiring more robust sub-idle performance synthesis solvers. The objective of this study, was to improve the accuracy and reliability of a current aero gas turbine sub-idle performance solver by studying each component in isolation through numerical simulations. Areas researched were: low-speed and locked-rotor com- pressor characteristics, low-power combustion efficiency, air blast atomizer and combustor performance at sub-idle, torque-based whole engine sub-idle performance synthesis, and mixer performance at far oﬀ-design conditions. The observations and results from the numerical simulations form the contribution to knowledge of this research. Numerical simulations of compressor blades under highly negative incidence angles show the complex nature of the flow, with the results used to determine a suitable flow deviation model, a method to extract blade aerodynamic char- acteristics in highly separated flows, and measure the blockage caused by highly separated flow with operating condition and blade geometry. The study also concluded that the use of Blade Element Theory is not accurate enough to be used at such far oﬀ-design con- ditions. The linearised parameter-based whole engine performance solver was converted to used torque-based parameters, which validated against engine test data, shows that it is suitable for low-power simulations with the advantage of having the potential to start engine simulations from static conditions. A study of air-blast atomization at windmilling relight conditions has shown that current established correlations used to predict spray characteristics are not suitable for altitude relight studies, tending to overestimate the atomization quality. Also discovered is the highly influential interaction of compressor wakes with the combustor and atomizer under altitude relight conditions, resulting in more favourable lighting conditions than previous assumptions and models have shown. This is a completely new discovery which will result in a change in the way combustors are designed and sized for relight conditions, and the way combustion rig tests are conducted. The study also has valuable industrial contributions. The locked-rotor numerical data was used within a stage-stacking compressible flow code to estimate the compressor sub- idle map, of which results were used within a whole engine performance solver and results validated against actual engine test data. The atomization studies at relight were used to factor in the insensitivity of current spray correlations, which together with a newly de- veloped sub-idle combustion efficiency sub-routine, are used to determine the combustion efficiency at low-power settings. The interaction of compressor wakes with the atomizer showed that atomizer performance at relight is underestimated, resulting in oversized combustors. By using the knowledge gained within this research, combustor size can be reduced, resulting in lower NOx at take-oﬀ and a smaller and lighter core, with a com- bustor requiring less cooling air. The component research has advanced the knowledge and modelling capability of sub-idle performance solvers, increasing their reliability and encouraging their use for future aero gas turbine engines.